A de novo translocation t(3;17)(q26.3;q23.1) in a child with Cornelia de Lange syndrome. Issue 9 (September 1991) - Ireland, M; English, C; Cross, I; Houlsby, W T; Burn, J
Abstract : A female infant with Cornelia de Lange syndrome and severe limb reduction defects is described. Chromosome analysis showed a de novo translocation with breakpoints at 3q26.3 and 17q23.1. This is the first reported case of a de novo translocation associated with this syndrome.